2012
DOI: 10.1038/cddis.2012.182
|View full text |Cite
|
Sign up to set email alerts
|

Functional cooperativity by direct interaction between PAK4 and MMP-2 in the regulation of anoikis resistance, migration and invasion in glioma

Abstract: Gliomas display anoikis resistance, enhanced invasion in to the adjacent brain parenchyma and eventually recur despite using the standard therapies. Our studies on increased anoikis sensitization in matrix metalloproteinase-2 (MMP-2)-knockdown 4910 and 5310 human glioma xenograft cells were interestingly correlated with p21-activated kinase 4 (PAK4) inhibition, prompting us to further investigate the role of PAK4 in glioma. Here, we report the PAK4 upregulation in positive correlation with increasing glioma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 53 publications
5
66
0
Order By: Relevance
“…Kesanakurti et al (11) observed that siRNA-mediated Pak4 knockdown inhibited invasion and migration by down-regulating MMP-2 in a human glioma model using xenograft cells. These findings are in agreement with our results in that the activity of Pak4 directly influences the expression of MMPs in endometrial tissues, and this may implicate Pak4 as an important biological promoter of the invasion of endometrial cells through regulation of the expression and/or activity of MMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kesanakurti et al (11) observed that siRNA-mediated Pak4 knockdown inhibited invasion and migration by down-regulating MMP-2 in a human glioma model using xenograft cells. These findings are in agreement with our results in that the activity of Pak4 directly influences the expression of MMPs in endometrial tissues, and this may implicate Pak4 as an important biological promoter of the invasion of endometrial cells through regulation of the expression and/or activity of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have demonstrated that increased expression of Pak4 is correlated with tumor progression or metastasis (10,11). We previously found that Pak4 immunoreactivity is significantly higher in the eutopic endometrium as well as ovarian endometrioma of women with advanced-stage endometriosis compared with control subjects (12).…”
mentioning
confidence: 89%
“…Pak4 is overexpressed and/or highly activated in various human cancer tissues and cell lines, including the lung, liver, choriocarcinoma, glioma, colon, breast, endometrial, ovary, prostate, pancreas, and GC [18,19,14,20,12,[21][22][23][24]. Several studies have assessed the prognostic value and therapeutic potential of Pak4 in reproductive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, p21-activated kinase 4 (PAK4), a specific receptor of Cdc42 and Rac, is of great interest because it does not only play roles in normal cellular functions, but also implicate in tumorigenesis when being overexpressed [4]. Increasing data have suggested that the aberrant expression of PAK4 is closely related to the progression and development of ovarian, prostate, breast cancers, colon and gastric cancers, choriocarcinoma, and glioma [5][6][7]. Moreover, the phosphorylation of PAK4 at ser474 was also found to be increased in human HCC cell lines including MHCC97H, MHCC97L, and HepG2 [8].…”
Section: Introductionmentioning
confidence: 99%